Assessing transformer health through analysis of dissolved gases in cooling oil - Nisworo, Sapto; Hasibuan, Arnawan; Isa, Muzamir; Nrartha, I Made Ari; Jannah, Misbahul; Muhammad, Muhammad (International Journal of Applied Power Engineering (IJAPE), 2024)
Gases can form within the insulation system for various reasons while a transformer is in operation. If these gases are not promptly and properly managed, they can negatively impact the transformer's performance. Using the dissolved gas analysis (DGA) method to identify and assess the type and quantity of dissolved gases in transformer oil can uncover potential issues within the transformer. This information is crucial for guiding preventive maintenance and necessary repairs. Dissolved gas analysis testing was conducted by extracting transformer oil samples to identify signs of disturbances in the transformer based on the dissolved gas content. This research was conducted at the Paiton plant operations and maintenance services division. The condition of transformers was assessed by analyzing dissolved gases using the Rogers ratio method. Results indicate that the transformer at Paiton 9 is in good condition but overheating has occurred and requires treatment. Conversely, the transformers at Paiton 1 and 2 are in poor condition, showing signs of electrical faults and excessive heat. Despite several attempts to add inhibitors and conduct frequent testing, the transformers remained in poor condition, necessitating their replacement or repair.